2017
DOI: 10.1038/s41598-017-00684-w
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GSN could decrease inflammation and apoptosis in EAE and may enhance vitamin D therapy on EAE/MS

Abstract: The decrease of gelsolin (GSN) in the blood has been reported in multiple sclerosis (MS) patients and experimental allergic encephalomyelitis (EAE) animals, but the protective effect of GSN on EAE/MS lacks of evidence. In our study, we increased the GSN level in EAE by injecting GSN-overexpress lentivirus (LV-GSN) into the lateral ventricle and caudal vein and found that GSN administration can delay the onset and decrease the severity of EAE. Vitamin D is proven to have a therapeutic effect on MS/EAE; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Saa5 plays a significant role in the acute phase response in animals suffering from infection or injury, and its transcript levels increased dramatically in rainbow trout with Yersinia ruckeri infection (66). In mammals, GSN is a crucial regulator of actin filament assembly and disassembly; however, recent evidence from mammals suggests that GSN inhibits the inflammatory and cytokine response induced by LPS and overexpression of GSN decreases inflammation and apoptosis in experimental allergic encephalomyelitis animals (67,68). Moreover, in agreement with our results, Eslamloo et al (31) also showed the decreased expression of gsn in Atlantic salmon infected with R. salmoninarum.…”
Section: P Salmonis Infection Affects Host Innate Immunitymentioning
confidence: 99%
“…Saa5 plays a significant role in the acute phase response in animals suffering from infection or injury, and its transcript levels increased dramatically in rainbow trout with Yersinia ruckeri infection (66). In mammals, GSN is a crucial regulator of actin filament assembly and disassembly; however, recent evidence from mammals suggests that GSN inhibits the inflammatory and cytokine response induced by LPS and overexpression of GSN decreases inflammation and apoptosis in experimental allergic encephalomyelitis animals (67,68). Moreover, in agreement with our results, Eslamloo et al (31) also showed the decreased expression of gsn in Atlantic salmon infected with R. salmoninarum.…”
Section: P Salmonis Infection Affects Host Innate Immunitymentioning
confidence: 99%
“…Furthermore, the combination of vitamin D and overexpressing GSN-lentiviruses causes a reduction of inflammation and even a delay in the onset of EAE in tested rats (Ref. 103).…”
Section: Gsn In Other Diseasesmentioning
confidence: 99%
“…Western blot was performed to verify the protein expression level of PRRT2 in hippocampus. The Western blotting analysis was carried out as previously described with minor modifications. Briefly, the rat hippocampus tissues were homogenized in 500 μL ice‐cold RIPA lysis buffer (Beyotime, Shenzhen, Guangdong, China) using a tissue homogenizer, followed by sonication for 10 s and centrifugation (20 min, 15 000 rpm, 4°C).…”
Section: Methodsmentioning
confidence: 99%